Prehospital whole blood reduces early mortality in patients with hemorrhagic shock. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Braverman, Maxwell A.; Smith, Alison; Pokorny, Douglas; Axtman, Benjamin; Shahan, Charles Patrick; Barry, Lauran; Corral, Hannah; Jonas, Rachelle Babbitt; Shiels, Michael; Schaefer, Randall; Epley, Eric; Winckler, Christopher; et al.
Abstract: Background: Low titer O+ whole blood (LTOWB) is being increasingly used for resuscitation of hemorrhagic shock in military and civilian settings. The objective of this study was to identify the impact of prehospital LTOWB on survival for patients in shock receiving prehospital LTOWB transfusion. Study design and methods: A single institutional trauma registry was queried for patients undergoing prehospital transfusion between 2015 and 2019. Patients were stratified based on prehospital LTOWB transfusion (PHT) or no prehospital transfusion (NT). Outcomes measured included emergency department (ED), 6‐h and hospital mortality, change in shock index (SI), and incidence of massive transfusion. Statistical analyses were performed. Results: A total of 538 patients met inclusion criteria. Patients undergoing PHT had worse shock physiology (median SI 1.25 vs. 0.95, p  < .001) with greater reversal of shock upon arrival (−0.28 vs. −0.002, p  < .001). In a propensity‐matched group of 214 patients with prehospital shock, 58 patients underwent PHT and 156 did not. Demographics were similar between the groups. Mean improvement in SI between scene and ED was greatest for patients in the PHT group with a lower trauma bay mortality (0% vs. 7%, p  = .04). No survival benefit for patients in prehospital cardiac arrest receiving LTOWB was found ( p  > .05). Discussion: This study demonstrated that trauma patients who received prehospital LTOWB transfusion had a greater improvement in SI and a reduction in early mortality. Patient with prehospital cardiac arrest did not have an improvement in survival. These findings support LTOWB use in the prehospital setting. Further multi‐institutional prospective studies are needed.